Effectiveness of marketing methods employed in pharmaceutical establishments - Ortiz Cardona , Johana Elvira
This research is focused on determining the effectiveness of the marketing method used by pharmaceutical establishments in the city of Medellín, zeroing on the different available strategies we have the following : customer relationship management (CRM) and social networks. The first being that which allows for personalized management of customers, improving loyalty and sales; on the other hand, social networks promote visibility, interactions and commitment to the brand. This study implies the research in different bibliographic sources and the application of a survey in other to identify marketing strategies used in the different establishments.